Responsible Research and Innovation Framework, the Nagoya Protocol and Other European Blue Biotechnology Strategies and Regulations: Gaps Analysis and Recommendations for Increased Knowledge in the Marine Biotechnology Community - Schneider, Xenia Theodotou; Stroil, Belma Kalamujić; Tourapi, Christiana; Rebours, Céline; Gaudêncio, Susana P.; Novoveská, Lucie; Vasquez Christodoulou, Marlen (My University, 2022)
As the quest for marine-derived compounds with pharmacological and biotechnological potential upsurges, the importance of following regulations and applying Responsible Research and Innovation (RRI) also increases. This article aims at: (1) presenting an overview of regulations and policies at the international and EU level, while demonstrating a variability in their implementation; (2) highlighting the importance of RRI in biodiscovery; and (3) identifying gaps and providing recommendations on how to improve the market acceptability and compliance of novel Blue Biotechnology compounds. This article is the result of the work of the Working Group 4 "Legal aspects, IPR and Ethics" of the COST Action CA18238 Ocean4Biotech, a network of more than 130 Marine Biotechnology scientists and practitioners from 37 countries. Three qualitative surveys ("Understanding of the Responsible Research and Innovation concept", "Application of the Nagoya Protocol in Your Research", and "Brief Survey about the experiences regarding the Nagoya Protocol") indicate awareness and application gaps of RRI, the Nagoya Protocol, and the current status of EU policies relating to Blue Biotechnology. The article categorises the identified gaps into five main categories (awareness, understanding, education, implementation, and enforcement of the Nagoya Protocol) and provides recommendations for mitigating them at the European, national, and organisational level.
Keywords: Nagoya Protocol; Responsible Research and Innovation (RRI); Blue biotechnology; Convention on biological diversity; Legal and ethical compliance workflow; Marine biotechnology; Marine genetic resources; Marine micro- and macro-organisms; Marine natural products; Policy recommendations; Sustainable blue economy